A Study of Normothermic Hemoperfusion of the Porcine Pancreas and Kidney. Issue 5 (22nd September 2016) - Kuan, Kean Guan; Wee, Mau Nam; Chung, Wen Yuan; Kumar, Rohan; Mees, Soeren Torge; Dennison, Ashley; Maddern, Guy; Trochsler, Markus
Abstract: Normothermic machine perfusion has enormous potential to improve organ preservation and expand the organ donor pool. It is well established in other organs but not the pancreas, which has especially strict organ acceptance criteria. We established a model of normothermic hemoperfusion of the porcine pancreas with and without addition of the kidney as a dialysis organ. Four pancreases were harvested and perfused for 120 min with autologous whole blood at body temperature, two with parallel perfusion of the kidney and two without. The organs and perfusion circuit were evaluated for gross appearance, pH, histology and perfusion parameters. The organs maintained steadily increasing flow rate and perfusion pressure. Gross appearance of the organs was stable but appeared grossly ischemic toward the end of the perfusion period. Histology demonstrated necrosis centered in acinar tissue but islet cells were preserved. pH was significantly alkalotic toward the end of the perfusion, likely due to pancreatic tissue damage. Addition of the kidney did not result in significant improvement of the acid–base environment in this small series. In conclusion, normothermic perfusion of the pancreas is still in the experimental stages but holds great potential. Further studies to optimize perfusion parameters will significantly improve results. Parallel perfusion of the kidney may facilitate improvement in the acid–base environment.